Hiding and Revealing: Text and Image in Venantius Fortunatus’s Carmina - Gina Derhard-Lesieur (Entangled Religions - Interdisciplinary Journal for the Study of Religious Contact and Transfer, 2023)
In his carmina, Venantius Fortunatus (sixth century) has left us three figurate poems that depict the cross as an image, while its verses describe the cross textually. He is thus an author who completely detaches figurate poems from the pagan tradition and inscribes them in the Christian one. The aim of this essay is to examine these poems from a pictorialist perspective. To this end, after a brief presentation of all three poems, they are considered, firstly, as ekphraseis that draw on a three-step representation: The figure depicts a cross that points to transcendence, the verses describe it, and they have the potential to evoke an additional mental image in the reader. Secondly, I examine what image and text, and thus the figurate poems as intermedial products, gain through the respective other medium. This results, thirdly, in an analysis of the figurate poems within the categories of iconism, aniconism, and anti-iconism.